Absorptive capacity, R&D spillovers, and public policy - Dermot Leahy; James Peter Neary (University College Dublin, Department of Economics, 2004)
Empirical evidence strongly suggests that R&D increases a firm's absorptive capacity (its ability to absorb spillovers from other firms) as well as contributing directly to profitability. We explore the theoretical implications of this. We specify a general model of the absorptive capacity process and show that costly absorption both raises the effectiveness of own R&D and lowers the effective spillover coefficient. This weakens the case for encouraging research joint ventures, even if there is complete information sharing between its members. It also implies an additional strategic pay-off to policies that raise the level of extra-industry knowledge.
hdl:10197/1312
Keywords: O31; L13; 330; Absorptive capacity of R&D; competition policy; industrial policy; R&D spillovers; research joint ventures